Tinjauan Atas 'Fungsi' Berdasarkan Filsafat Matematika - Manalaksak, Dwin Gideon (Jurnal Filsafat "WISDOM", 2004)
Definition of "Function" is mapping from domain to range. "Function" can be divided on logical function, mathematical function, and propotional function. Through the detectable functions man can find a systematic way to construct good reasoning. That "Function" can be resulted from a qualitative progress in which human get her/his knowledge. The systematization of that human action in acquiring knowledge will from the "function"